Direct measurements of adhesion forces of water droplets on smooth and patterned polymers. Issue 1 (8th November 2017) - Sun, Yujin; Jiang, Youhua; Choi, Chang-Hwan; Xie, Guangyuan; Liu, Qingxia; Drelich, Jaroslaw W
Abstract : A microelectronic balance system was employed to measure the force of spreading (snap-in force) during water droplet attachment and spreading on polymer surfaces and the water–polymer adhesion forces (maximum adhesion and pull-off forces) after droplet compression, retreat and detachment. Equipped with a charge-coupled device camera and data acquisition software, the instrument measured directly the forces; monitored droplet–surface separation, including distances over which droplet stretched; and collected optical images simultaneously. The images were used to analyze capillary and surface tension forces based on measured droplet shape, surface curvature, droplet base radius and values of contact angles. The forces measured with the microbalance were compared to calculated capillary/surface tension forces. Nearly excellent agreement between directly measured and calculated forces was verified for polymers with smooth surfaces. Experiments with patterned polymers with pores and pillars revealed that interpretation of forces requires knowledge of a triple-contact-line characteristic. One relevant parameter, named normalized contact line length, was introduced to surface tension forces to quantify forces measured directly with a microbalance.